Preparation method of medical degradable zinc alloy GBR film coated with multi-layer MXene phase zinc phosphate coating
The medical degradable zinc alloy GBR film coated with a multi-layer MXene phase zinc phosphate coating solves the shortcomings of existing barrier films in terms of tensile strength and space maintenance capabilities, and achieves efficient space support and space maintenance for bone tissue growth. Good cytocompatibility.
Patent Information
- Application Number
- CN202211583114.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-09
- Publication Date
- 2025-01-21
- Estimated Expiration
- 2042-12-09
AI Technical Summary
The existing degradable barrier membranes have shortcomings in tensile strength and spatial maintenance capabilities, which are difficult to meet the long-term stable spatial support function of bone tissue growth, and may trigger inflammation and foreign body reactions during the degradation process.
The medical degradable zinc alloy GBR film coated with a doped multi-layer MXene phase zinc phosphate coating is made of high-purity metal Zn and trace elements Cu, Ti, etc. as raw materials, and is melted in a pit furnace and homogenized in a muffle furnace. Preparation by hot rolling deformation, chemical deposition and other steps.
It achieves high coating bonding strength, good mechanical-corrosion stability, controllable degradation rate, excellent cell compatibility and osteogenic properties, and has the potential of a new generation of degradable biomedical materials.
Smart Images

Figure CN116196470B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of biomedical metal technology, and in particular to a method for preparing a medical degradable zinc alloy GBR film coated with a multi-layer MXene-doped zinc phosphate coating. Background Art
[0002] With the development and widespread application of oral implant technology, the problem of tooth loss has been greatly solved. However, due to traumatic damage to teeth, osteoporosis, alveolar ridge atrophy caused by severe periodontitis, and insufficient bone mass, bone defects, poor implant retention caused by diseases such as tumor surgery and diabetes, dental implant failure is easy to occur. In order to meet the needs of this part of patients, bone augmentation is a practical solution. At present, guided bone regeneration (GBR) and guided tissue regeneration (GTR) technologies are mostly used for clinical treatment to achieve successful aesthetic implant restoration. Therefore, for oral treatment applications, the key to GBR / GTR technology is that the barrier membrane needs to have many characteristics: 1. It has a barrier effect and can establish and maintain bone regeneration space for transplant materials; 2. Good blood supply accelerates bone repair regeneration in the defect area; 3. Good postoperative anti-infection and antibacterial properties; 4. Good biocompatibility and bone induction properties; 5. The repair material has good plasticity, simple operation, and small surgical trauma. At present, barrier membrane materials can be divided into two categories: absorbable membranes and non-absorbable membranes. Non-degradable barrier membranes such as titanium and titanium alloys, polytetrafluoroethylene, etc. have become common materials in the medical field due to their high strength, good biocompatibility, and strong corrosion resistance. However, due to their non-degradability, permanently implanted barrier membranes cannot be absorbed by the body, and secondary removal surgery is required after the treatment. At the same time, this barrier membrane has a high risk of infection and induces a large proportion of complications in clinical applications, such as mucosal rupture, membrane exposure, infection, etc., which ultimately lead to osteogenesis failure. In addition, titanium and polytetrafluoroethylene barrier membranes also have complex preparation processes and high costs, which limits their clinical application. In contrast, degradable barrier membranes such as organic synthetic polymer membranes and animal-derived collagen can be self-degraded and absorbed through body fluids and enzyme interactions, avoiding secondary removal surgery and reducing patient pain and economic burden. In addition, degradable barrier membranes also have moderate coagulability, weak immunogenicity, good biocompatibility and bone induction, which help promote the proliferation and healing of bone tissue, especially collagen membranes. However, existing degradable organic and collagen membranes have low tensile strength and poor spatial maintenance ability, which makes them prone to membrane collapse and displacement, making it difficult to meet the long-term stable spatial support function of bone tissue growth. At the same time, an acidic environment will form around the membrane during the degradation process, which may cause inflammation and foreign body reaction, and even require surgical debridement to remove it. In addition, although degradable barrier membranes are degradable, they degrade quickly, which limits their application in bone augmentation. For example, collagen membranes usually degrade within 1-4 weeks.
[0003] As a biomaterial that has been widely studied in recent years, degradable metals have better mechanical strength and stability than polymers. Therefore, degradable metals have both the high mechanical stability of titanium alloys and the degradable properties of degradable polymers, and are widely used in bone tissue repair, bone fixation, and interventional stents. At present, the research on degradable metals is mainly carried out around magnesium alloys, zinc alloys, and iron-based alloys, which are essential nutrients for the human body. Pure magnesium and its alloys have good mechanical properties, biocompatibility, and osteogenic properties. They can be degraded and absorbed in the human body. Since they can effectively integrate acidic substances to increase pH during their degradation, they have certain antibacterial ability. However, magnesium alloys have a too fast degradation rate and produce a large amount of hydrogen, which cannot maintain bone regeneration space during their service period in the body. At the same time, although magnesium alloys have certain antibacterial ability, their antibacterial properties are still relatively weak. When the infection is more serious, the possibility of GBR surgery failure is relatively high. Iron has the highest standard electrode potential of -0.447V among the three metals, which makes the degradation rate of most iron-based alloys slow. At the same time, the dense degradation products covering the surface of the implant are difficult to be completely degraded in the body, further reducing the degradation rate of the iron-based alloy medical implant, seriously hindering the proliferation of bone tissue and losing the advantages of degradable metals. Pure zinc and its alloys have a moderate degradation rate among the three metals, which can better balance the degradation rate and mechanical stability of the implant. At the same time, the Zn element participates in a large number of physiological reaction processes such as human cell development and growth, gene expression, immune system and nervous system. In addition to maintaining normal physiological functions, zinc also has bone promotion functions. However, due to its poor mechanical properties and rigidity, pure zinc is difficult to meet the purpose of stable support of the barrier membrane. In addition, there is a problem of poor biological activity caused by excessive local release concentration of Zn ions during the degradation process. Therefore, in order to ensure that the tissue cells around the implant can migrate, adhere, proliferate and differentiate normally in the early stage of implantation, it is necessary to control the initial corrosion of the zinc matrix and the initial release of zinc ions to improve the biocompatibility of zinc-based implants. In addition, the mechanical properties of cast zinc alloys are poor, which is difficult to meet the mechanical properties requirements of existing clinical implants. The effective means at present are alloying treatment and surface treatment. Surface phosphating can significantly improve the corrosion resistance and biocompatibility of pure zinc and zinc alloys. However, due to the weak bonding between phosphate coating and zinc alloy and the easy cracking, it is difficult to ensure the mechanical stability of zinc alloy and the long-term effectiveness of coating. Therefore, improving the mechanical-corrosion stability, bonding ability and bending resistance of phosphate coating is an urgent problem to be solved.
[0004] At present, there is no report in domestic and foreign literature on the preparation method and corresponding performance research of medical degradable zinc alloy (GBR) membrane coated with multi-layer MXene phase zinc phosphate coating, so it is proposed to use medical degradable zinc alloy (GBR) membrane as the next stage of oral GBR surgery. Summary of the invention
[0005] In view of the shortcomings of the prior art, the purpose of the present invention is to provide a method for preparing a medical degradable zinc alloy GBR film coated with a multilayer MXene phase zinc phosphate coating to solve the above problems. The technical solution of the present invention is implemented as follows: a medical degradable zinc alloy GBR film coated with a multilayer MXene phase zinc phosphate coating, the MXene phase is M2XTy, M3XTy, M3X2Ty and M4X3Ty phase, and M is one or more of Ti, Nb, Zr, Mo, Sc and Hf with good biological activity. Further, M is one or more of Ti, Nb, Zr, Mo, Sc and Hf with good biological activity. Further, X is one or both of C and N. Further, T is one or more of non-toxic Ga, Ge, Si, P, Sn and In, and the y content is 1 or 2. Furthermore, the zinc alloy is pure zinc or Zn-x alloy, x is one or more of Cu, Mg, Sr, Ca, Ge, Ti, Se, Li, Fe, Sn, Ag, Mn, RE, which are non-toxic to human body, and the mass percentage of the trace element x is 0.1-6%. In addition, the present application also provides a method for preparing a medical degradable zinc alloy GBR membrane coated with a multi-layer MXene phase doped zinc phosphate coating, comprising the following steps: a. Using high-purity metal Zn and x as raw materials, and weighing them according to the mass ratio of the elements in the Zn-x alloy composition; b. Placing the raw materials in a pit furnace and heating them to 500-700°C for melting and then casting them into ingots; c. Placing the ingots in a muffle furnace heated to 250-350°C for homogenization treatment for 2-20 hours, and cooling them by air cooling, water cooling or furnace cooling; d. Cutting a strip sample with a thickness of 5-10 mm from the ingot, placing the strip sample in a muffle furnace at 280-350°C for 20-60 minutes for preheating, and then performing rough rolling and finish rolling hot rolling deformation in sequence; e. Grinding with sandpaper to remove surface oxides, and rinsing with deionized water and alcohol and then drying. Then, under the action of ultrasound, the zinc alloy film is immersed in a phosphoric acid solution heated to 20-50°C for deposition for 10-30 minutes; f. After chemical deposition, the zinc alloy film is taken out, rinsed with deionized water and alcohol, and then dried, and finally a zinc alloy GBR film with a surface coated with a multilayer MXene phase-doped zinc phosphate coating is obtained. Further, the rough rolling uses a two-roll mill to roll the strip sample into a plate with a deformation variable of 60-80%, the deformation variable of each pass is 5-10%, and the preheating is performed for 3-10 minutes before rolling. The finishing rolling uses a six-roll mill to roll the plate into a zinc alloy film with a deformation variable of 80-99%, the deformation variable of each pass is 1-5%, and the preheating is performed for 2-5 minutes before rolling. Further, the phosphoric acid solution contains 10-30 g / L phosphoric acid, 15-45 g / L zinc nitrate hexahydrate, and 2-10 g / L multilayer MXene phase, and the pH value is adjusted to 2-4 with a dilute hydrochloric acid solution.Furthermore, in step e, the strip sample is dried and air-dried for 5 to 10 minutes by a drying device, and the drying device includes: a machine body; a first rotating shaft, rotatably connected to the upper end of the machine body, the first rotating shaft is vertically arranged, the lower end of the first rotating shaft passes through the upper end of the machine body, extends to the inside of the machine body and is fixedly connected to a first pulley; a first driving motor is fixedly installed on a side of the upper end of the machine body away from the first rotating shaft, the output shaft of the first driving motor passes through the upper end of the machine body, extends to the inside of the machine body and is fixedly connected to a second pulley; a support disk, fixedly installed on the upper end of the first rotating shaft, and a plurality of clamping mechanisms for clamping the zinc alloy film are circumferentially arranged on the edge of the lower end of the support disk; a transparent cover, which is arranged on the outside of the first rotating shaft and the support disk; an air inlet; a feed inlet, the air inlet and the feed inlet are both opened on the side wall of the transparent cover; a hot air blower, fixedly installed in the air inlet; wherein the air inlet, the feed inlet and the clamping mechanism are at the same horizontal height, and an exhaust hole is opened at the upper end of the transparent cover. Furthermore, the clamping device includes: a vertical plate, fixedly mounted on the lower end edge of the support plate; two first horizontal plates, fixedly mounted on both sides of the lower edge of one end of the vertical plate away from the first rotating shaft; two second horizontal plates, fixedly mounted on both sides of the upper edge of one end of the vertical plate away from the first rotating shaft; a second driving motor is fixedly mounted on the outer side of one of the second horizontal plates, one end of the output shaft of the first driving motor passes through its corresponding second horizontal plate and extends to the other second horizontal plate; a cam, fixedly mounted on the output shaft of the second driving motor and located between the two second horizontal plates; the second rotating shaft, rotatably connected between the two first horizontal plates; a swinging plate, integrally formed in the middle of the second rotating shaft, the second rotating shaft is located at one-third of the length of the swinging plate relative to the swinging plate; an elastic clamping arm, fixedly mounted on one end of the swinging plate away from the second rotating shaft; a connecting rod, hinged on a side of the upper end of the swinging plate away from the elastic clamping arm; a slide groove, circumferentially opened on the outer side of the cam; wherein the upper end of the connecting rod is slidably connected in the slide groove. The beneficial effects of the present invention are as follows: the multilayer MXene phase-doped zinc phosphate coating prepared by the present invention is used to prepare a degradable GBR membrane, which has high coating bonding strength, good mechanical-corrosion stability, controllable degradation rate, excellent cell compatibility and osteogenic performance, and is expected to become a new generation of potential degradable biomedical materials. BRIEF DESCRIPTION OF THE DRAWINGS
[0006] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative labor.
[0007] Figure 1 The SEM images and EDS analysis images of the surface and cross section of the zinc alloy GBR film covered with a multilayer MXene phase-doped zinc phosphate coating according to a specific embodiment of the present invention;
[0008] Figure 2 This is a surface SEM image of a zinc alloy GBR film sample coated with a multi-layer MXene phase-doped zinc phosphate coating after a tensile test in a specific embodiment of the present invention;
[0009] Figure 3 This is a quasi-in-situ SEM image of a zinc alloy GBR film coated with a multilayer MXene-doped zinc phosphate coating after being bent at different angles in a specific embodiment of the present invention;
[0010] Figure 4 Polarization curves of zinc alloy GBR film and zinc alloy GBR film coated with multi-layer MXene phase-doped zinc phosphate coating in Hanks' solution and artificial saliva according to a specific embodiment of the present invention;
[0011] Figure 5 It is a cross-sectional view of a drying device according to a specific embodiment of the present invention;
[0012] Figure 6 It is an isometric view of a drying device according to a specific embodiment of the present invention;
[0013] Figure 7 It is a partial enlarged view of the specific implementation mode A of the present invention. DETAILED DESCRIPTION
[0014] The following will be combined with the drawings in the embodiments of the present application to clearly describe the technical solutions in the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present application. In the description of the present application, it should be noted that the terms used here are only for describing specific embodiments, and are not intended to limit the exemplary embodiments according to the present application. For ease of description, the sizes of the various parts shown in the drawings are not drawn according to the actual proportional relationship. The techniques, methods and devices known to ordinary technicians in the relevant fields may not be discussed in detail, but in appropriate cases, the techniques, methods and devices should be regarded as part of the authorization specification. In all the examples shown and discussed here, any specific value should be interpreted as merely exemplary, not as a limitation. Therefore, other examples of the exemplary embodiments may have different values. It should be noted that similar reference numerals and letters represent similar items in the following drawings, so once an item is defined in one drawing, it does not need to be further discussed in the subsequent drawings.
[0015] Embodiment 1:
[0016] like Figures 1 to 4As shown, the present invention discloses a method for preparing a medical degradable zinc alloy GBR film coated with a multilayer MXene phase zinc phosphate coating. First, high-purity metal Zn, Cu and Zn-2Ti are used as raw materials, and the weights are weighed according to the mass ratio of the single substances in the Zn-1Cu-0.1Ti alloy composition. Then, the raw materials are placed in a pit furnace and heated to 600°C for melting and then cast into an ingot. Then, the ingot is placed in a muffle furnace heated to 340°C for homogenization for 10 hours and air-cooled. A strip sample with a thickness of 10 mm is cut from the ingot, and the strip sample is first placed in a muffle furnace at 280°C for 20 minutes for preheating, and then hot-rolled by rough rolling and finishing rolling in sequence. The rough rolling uses a two-roll rolling mill to roll the strip sample into a plate with a deformation variable of 80%, and the deformation variable of each pass is 10% and preheated for 5 minutes before rolling. The finishing rolling uses a six-roll mill to roll the plate into a zinc alloy film with a deformation variable of 98%, a deformation variable of 2% per pass, and a preheating of 3 minutes before rolling. Then, the surface oxide is removed by sandpaper polishing, and then rinsed with deionized water and alcohol and dried. Then, the zinc alloy film is immersed in a phosphoric acid solution heated to 40°C for deposition for 20 minutes under the action of ultrasound. The phosphoric acid solution contains 20g / L phosphoric acid, 30g / L zinc nitrate hexahydrate, and 5g / L multilayer Ti2CSi phase, and the pH value is adjusted to 3 with a dilute hydrochloric acid solution. After chemical deposition, the zinc alloy film is taken out, rinsed with deionized water and alcohol, and dried, and finally a zinc alloy GBR film with a surface coated with a multilayer MXene phase-doped zinc phosphate coating is obtained.
[0017] Implementation Effect
[0018] from Figure 1It can be seen from the SEM image that the needle-shaped and flake-shaped multilayer MXene phase-doped zinc phosphate coating is evenly covered on the surface of the Zn-1Cu-0.1Ti alloy film. The EDS analysis results show that the coating contains a large amount of O, Zn and P elements, and the Zn / P atomic ratio is close to 1.5. The cross-sectional morphology and corresponding EDS energy spectrum of the zinc alloy GBR film with multilayer MXene phase-doped zinc phosphate coating show that a uniform and dense multilayer MXene phase-doped zinc phosphate coating with a thickness of 3.3μm is covered on the surface of the sample, and no obvious cracks are observed. A large amount of Zn, P and O elements are evenly distributed in the coating, while the Zn-1Cu-0.1Ti matrix contains a large amount of Zn and a small amount of Cu and Ti. From the mechanical properties in Table 1, it can be seen that the tensile strength of the zinc alloy GBR film is 298MPa, the yield strength is 254MPa, and the elongation is 33.4%. The tensile strength of the zinc alloy GBR membrane coated with a multilayer MXene phase-doped zinc phosphate coating is 315MPa, the yield strength is 267MPa, and the elongation is 36.2%. After being immersed in artificial saliva for 1 month, the tensile strength of the zinc alloy GBR membrane is 277MPa, the yield strength is 235MPa, and the elongation is 29.0%. The tensile strength of the zinc alloy GBR membrane coated with a multilayer MXene phase-doped zinc phosphate coating is 297MPa, the yield strength is 245MPa, and the elongation is 31.3%. The specimens all have high strength and toughness matching and all exceed the requirements of a yield strength greater than 230MPa and an elongation greater than 15% for degradable bone implant materials.
[0019] Table 1: Mechanical properties of zinc alloy GBR membrane and zinc alloy GBR membrane coated with multilayer MXene phase doped zinc phosphate coating before and after immersion in artificial saliva for 1 month
[0020]
[0021] from Figure 2 It can be seen from the SEM image of the surface at the tensile fracture that the coating fracture surface of the zinc alloy GBR film tensile specimen covered with coating is roughly parallel to the tensile fracture surface. The length of the fracture area is only 590μm, and a large amount of coating still exists on the surface of the specimen, indicating that the multilayer MXene phase-doped zinc phosphate coating has good bonding strength and deformation resistance.
[0022] from Figure 3It can be seen from the quasi-in-situ SEM images of the multilayer MXene phase-doped zinc phosphate coating after different bending that there are basically no cracks, holes and uncovered areas on the surface of the coating when it is not bent and deformed, indicating that the coating completely covers the surface of the Zn-1Cu-0.1Ti film and has good bonding strength. When bent to 90°, a large number of horizontal cracks of different widths appear in the coating, and the cracks gradually decrease and become thinner along the maximum deformation area (90° bend vertex) to the two side planes. At the same time, the cracks extend along the fine cracks of the original coating and partially or completely penetrate the coating. After bending to 90° and returning to 0°, the crack width on the coating is significantly reduced, and even some fine cracks are healed, with no obvious coating collapse and shedding, showing good anti-deformation and healing effects, which is crucial for the shaping process during oral GBR surgery.
[0023] from Figure 4 It can be seen from the polarization curve and the corrosion parameters obtained by fitting the Tafel interval in the figure (see Table 2) that the zinc alloy GBR film with a covering coating obtained by polarization tests in Hanks' and artificial saliva solutions has a more positive corrosion potential, a lower corrosion current density and corrosion rate, and a lower degradation rate after immersion in the two solutions for 1 month, showing better corrosion resistance.
[0024] Table 2: Electrochemical performance parameters of the zinc alloy GBR membrane fitted after polarization test and the zinc alloy GBR membrane coated with multilayer MXene phase doped zinc phosphate coating in Hanks' solution and artificial saliva
[0025]
[0026] After culturing L929 cells in the extracts of 100%, 50% and 25% zinc alloy GBR membrane and coated zinc alloy GBR membrane for 3 days, the cell viability was 24.6% and 92.6%, 85.9% and 102.6%, 96.7% and 114.3%, respectively. The coated zinc alloy GBR membrane showed good cell compatibility.
[0027] Example 2
[0028] First, high-purity metal Zn, Cu and Zn-2Ti are used as raw materials, and the weight ratio of the single substances in the Zn-1Cu-0.1Ti alloy composition is weighed. Then the raw materials are placed in a pit furnace and heated to 650℃ for melting and then cast into ingots. Then the ingot is placed in a muffle furnace heated to 320℃ for homogenization for 10 hours and water-cooled. A strip sample with a thickness of 8mm is cut from the ingot. First, the strip sample is placed in a muffle furnace at 320℃ for 30 minutes for preheating, and then hot rolling deformation is carried out in sequence by rough rolling and finishing rolling. Among them, the rough rolling uses a two-roll mill to roll the strip sample into a plate with a deformation variable of 70%, the deformation variable of each pass is 5%, and the preheating is carried out for 10 minutes before rolling. The finishing rolling uses a six-roll mill to roll the plate into a zinc alloy film with a deformation variable of 95%, the deformation variable of each pass is 5%, and the preheating is carried out for 5 minutes before rolling.
[0029] Then, the surface oxide was removed by sandpaper polishing, and then rinsed with deionized water and alcohol and dried. Then, the zinc alloy film was immersed in a phosphoric acid solution heated to 40°C for deposition for 30 minutes under ultrasonic action. The phosphoric acid solution contained 10g / L phosphoric acid, 20g / L zinc nitrate hexahydrate, and 10g / L multilayer Zr3N2Ge phase, and the pH value was adjusted to 2.5 with a dilute hydrochloric acid solution. After chemical deposition, the zinc alloy film was taken out, rinsed with deionized water and alcohol, and dried, and finally a zinc alloy GBR film with a surface coated with a multilayer MXene phase-doped zinc phosphate coating was obtained.
[0030] The surface of the sample is covered with a uniform and dense multilayer MXene phase-doped zinc phosphate coating with a thickness of 6.2μm, and no obvious cracks are observed. The tensile strength of the zinc alloy GBR film coated with a multilayer MXene phase-doped zinc phosphate coating before and after immersion in artificial saliva is 308MPa and 299MPa, the yield strength is 252MPa and 253MPa, and the elongation is 28.9% and 25.3%. The corrosion potential, corrosion current density and corrosion rate of the zinc alloy GBR film covered with the coating obtained by polarization tests in Hanks' and artificial saliva solutions are -0.859V and -0.887V, 5.2μA / cm2 and 14.9μA / cm2, 72μm / y and 208μm / y, respectively. The degradation rate after immersion in Hanks' and artificial saliva solutions for one month is 33μm / y and 45μm / y. After L929 cells were cultured in the extracts of zinc alloy GBR membranes with concentrations of 100%, 50% and 25% covering coating for 3 days, the cell viability was 82.6%, 98.9% and 104.8%, respectively, showing good cell compatibility.
[0031] Embodiment 3:
[0032] like Figures 5 to 7As shown, this embodiment provides a method for preparing a medical degradable zinc alloy GBR film coated with a multilayer MXene phase doped zinc phosphate coating, which, in addition to the technical solutions of the above embodiments, also has the following technical features:
[0033] In the embodiment of the present invention, in step e, the strip sample is dried for 5 to 10 minutes by a drying device, and the drying device comprises:
[0034] Body 1;
[0035] A first rotating shaft 2 is rotatably connected to the upper end of the machine body 1. The first rotating shaft 2 is vertically arranged. The lower end of the first rotating shaft 2 passes through the upper end of the machine body 1 and extends to the inside of the machine body 1 and is fixedly connected to a first pulley 3.
[0036] A first drive motor 4 is fixedly mounted on a side of the upper end of the body 1 away from the first rotating shaft 2, and an output shaft of the first drive motor 4 passes through the upper end of the body 1 and extends to the inside of the body 1 and is fixedly connected to a second pulley 5;
[0037] The support plate 6 is fixedly mounted on the upper end of the first rotating shaft 2, and a plurality of clamping mechanisms for clamping the zinc alloy film are arranged around the lower edge of the support plate 6;
[0038] A transparent cover 7 is arranged outside the first rotating shaft 2 and the supporting plate 6;
[0039] Air inlet 8;
[0040] The feed inlet 9, the air inlet 8 and the feed inlet 9 are all opened on the side wall of the transparent cover 7;
[0041] A hot air blower 10 is fixedly installed in the air inlet 8;
[0042] The air inlet 8 , the material feed port 9 and the clamping mechanism are at the same level, and an exhaust hole 11 is opened at the upper end of the transparent cover 7 .
[0043] By adopting the above technical solution, the support plate is driven to rotate by the first driving motor and cooperates with the hot air blower and the clamping mechanism to quickly remove the deionized water and alcohol attached to multiple strip samples at one time, thereby effectively improving the drying effect and preparation efficiency and preventing the strip samples from being incompletely dried and affecting the subsequent chemical deposition effect.
[0044] Embodiment 4:
[0045] This embodiment provides a method for preparing a medical degradable zinc alloy GBR film coated with a multi-layer MXene phase doped zinc phosphate coating. In addition to the technical solutions of the above embodiments, it also has the following technical features:
[0046] In an embodiment of the present invention, the clamping device comprises:
[0047] The vertical plate 12 is fixedly mounted on the lower edge of the support plate 6;
[0048] Two first horizontal plates 13 are fixedly mounted on both sides of the lower edge of the vertical plate 12 which is away from the first rotating shaft 2;
[0049] Two second horizontal plates 14 are fixedly mounted on both sides of the upper edge of the vertical plate 12 which is away from the first rotating shaft 2;
[0050] The second drive motor 15 is fixedly mounted on the outer side of one of the second transverse plates 14 , and one end of the output shaft of the first drive motor 15 passes through the corresponding second transverse plate 14 and extends to the other second transverse plate 14 ;
[0051] The cam 16 is fixedly mounted on the output shaft of the second driving motor 15 and is located between the two second transverse plates 14;
[0052] A second rotating shaft 17, rotatably connected between the two first transverse plates 13;
[0053] The swing plate 18 is integrally formed in the middle of the second rotating shaft 17, and the second rotating shaft 17 is located at one third of the length of the swing plate 18 relative to the swing plate 18;
[0054] The elastic clamp arm 19 is fixedly mounted on one end of the swing plate 18 away from the second rotating shaft 17;
[0055] The connecting rod 20 is hinged to the upper end of the swing plate 18 and the side away from the elastic clamp arm 19;
[0056] The slide groove 21 is circumferentially opened on the outer side of the cam 16;
[0057] The upper end of the connecting rod 20 is slidably connected in the sliding groove 21 .
[0058] By adopting the above technical solution, the cam is driven to rotate by the second driving motor, and the cam drives the swing plate to move through the connecting rod to realize the swing of the elastic clamp arm, thereby further improving the separation effect of deionized water and alcohol from the strip sample. At the same time, the drying device can also be used for drying the zinc alloy film after chemical deposition, and the use effect is good.
[0059] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a medical degradable zinc alloy GBR film coated with a multilayer MXene phase zinc phosphate coating, characterized in that: MXene phases are M2XTy, M3XTy, M3X2Ty and M4X3Ty phases, where M is one or more of Ti, Nb, Zr, Mo, Sc and Hf with good bioactivity; X is one or both of C and N; T is one or more of non-toxic Ga, Ge, Si, P, Sn and In, and the value of y is 1 or 2; The zinc alloy is a Zn-x alloy, wherein x is one or more of the non-toxic elements Cu, Mg, Sr, Ca, Ge, Ti, Se, Li, Fe, Sn, Ag, Mn, and RE, and the mass percentage of x is 0.1-6%; The preparation method comprises the following steps: a. Use high-purity metal Zn and x as raw materials and weigh them according to the mass ratio of the single substances in the Zn-x alloy composition; b. Place the raw materials in a pit furnace and heat them to 500~700℃ to melt them and then cast them into ingots; c. Place the ingot in a muffle furnace heated to 250-350°C for homogenization for 2-20 hours, and cool it by air cooling, water cooling or furnace cooling; d. Cut a strip sample with a thickness of 5-10 mm from the ingot, place the strip sample in a muffle furnace at 280-350°C for 20-60 minutes for preheating, and then perform hot rolling deformation in sequence of rough rolling and finish rolling; e. Use sandpaper to remove the surface oxide, rinse with deionized water and alcohol and dry, then immerse the zinc alloy film in phosphoric acid solution heated to 20-50°C under ultrasonic action for 10-30 minutes; f. After chemical deposition, the zinc alloy film is taken out, rinsed with deionized water and alcohol respectively, and then dried, and finally a zinc alloy GBR film with a multi-layer MXene-doped zinc phosphate coating on the surface is obtained; The phosphoric acid solution contains 10-30 g / L phosphoric acid, 15-45 g / L zinc nitrate hexahydrate and 2-10 g / L multilayer MXene phase, and the pH value is adjusted to 2-4 with a dilute hydrochloric acid solution.
2. The method for preparing a medical degradable zinc alloy GBR film coated with a multi-layer MXene phase zinc phosphate coating according to claim 1, characterized in that: The rough rolling uses a two-roll mill to roll the strip sample into a plate with a deformation variable of 60~80%, the deformation variable of each pass is 5~10%, and the plate is preheated for 3~10 minutes before rolling. The finishing rolling uses a six-roll mill to roll the plate into a zinc alloy film with a deformation variable of 80~99%, the deformation variable of each pass is 1~5%, and the plate is preheated for 2~5 minutes before rolling.
Citation Information
Patent Citations
Preparation and application of MXenes biological coating with good biocompatibility
CN115177791A